2014
DOI: 10.3758/s13421-014-0495-x
|View full text |Cite
|
Sign up to set email alerts
|

Phonological similarity and orthographic similarity affect probed serial recall of Chinese characters

Abstract: The previous literature on working memory (WM) has indicated that verbal materials are dominantly retained in phonological representations, whereas other linguistic information (e.g., orthography, semantics) only contributes to verbal WM minimally, if not negligibly. Although accumulating evidence has suggested that multiple linguistic components jointly support verbal WM, the visual/orthographic contribution has rarely been addressed in alphabetic languages, possibly due to the difficulty of dissociating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…Moreover, the phonological similarity effect was removed by concurrent articulation, but the visual similarity effect remained intact, or was enhanced when articulatory rehearsal was prevented. Similar findings of independent phonological and visual similarity effects, and selective disruption of phonological but not visual similarity by concurrent articulation, have been reported recently by Lin, Chen, Lai and Wu ( 2015 ) using a probe technique to test memory for serial order of Chinese characters. Further evidence for the use of visual codes in serial recall tasks comes from the finding that serial recall of sequences of matrix patterns (Avons & Mason, 1999 ; Walker, Hitch & Duroe, 1993 ), and of faces (Smyth, Hay, Hitch & Horton, 2005 ) is disrupted when stimuli are visually similar.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Moreover, the phonological similarity effect was removed by concurrent articulation, but the visual similarity effect remained intact, or was enhanced when articulatory rehearsal was prevented. Similar findings of independent phonological and visual similarity effects, and selective disruption of phonological but not visual similarity by concurrent articulation, have been reported recently by Lin, Chen, Lai and Wu ( 2015 ) using a probe technique to test memory for serial order of Chinese characters. Further evidence for the use of visual codes in serial recall tasks comes from the finding that serial recall of sequences of matrix patterns (Avons & Mason, 1999 ; Walker, Hitch & Duroe, 1993 ), and of faces (Smyth, Hay, Hitch & Horton, 2005 ) is disrupted when stimuli are visually similar.…”
Section: Introductionsupporting
confidence: 87%
“…The above findings, and particularly the findings from Saito et al ( 2008 ) and Lin et al ( 2015 ), are consistent with neuropsychological evidence that immediate serial recall based on phonological codes and immediate serial recall based on visual codes might rely on separate, domain-specific temporary memory stores. For example, there are several reports of brain-damaged individuals with a specific impairment of verbal serial-ordered recall who also fail to show disruptive effects of phonological similarity with auditory presentation.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…This perhaps echoes some of the effects of temporal grouping explored by Spurgeon et al (2015). Lin, Chen, Lai, and Wu (2015) used a limited set of Chinese characters and demonstrated that both the phonological and orthographic similarity of the items resulted in poorer probed serial recall performance than occurred when the items were phonologically or orthographically distinct. Both of these studies suggest that the physical characteristics of stimuli affect immediate memory for serial order.…”
Section: Contributions To This Issuementioning
confidence: 60%
“…Healthy individuals are then thought to have available a temporary representation of the words based on other characteristics such as their visual appearance or their meaning (e.g. Lin, Chen, Lai, & Wu, 2015;Logie, Della Sala, Wynn, & Baddeley, 2000;Logie, Saito, Morita, Varma, & Norris, 2016;Saito, Logie, Morita, & Law, 2008;Tree, Longmore, Majerus, & Evans, 2011). In the case of PV, and for a previous case with similar impairments, KF 1972), as well as the more recent case of CT (Tree & Playfoot, 2019), when words were presented visually, immediate serial ordered recall was better than with auditory presentation.…”
Section: Case Studies Of Verbal Short-term Memory Impairmentmentioning
confidence: 99%